Computing the broadband vibroacoustic response of arbitrarily thick layered panels by a wave finite element approach - Chronopoulos, Dimitrios; Ichchou, M.; Troclet, B.; Bareille, O. (Elsevier, 2014)
A robust procedure for the prediction of the dynamic response of layered panels within a SEA wave-context approach is proposed hereby. The dispersion characteristics of two dimensional composite orthotropic structures are predicted using a Wave Finite Element method. By manipulating the mass and stiffness matrices of the modelled structural segment a polynomial eigenvalue problem is formed, the solutions of which correspond to the propagation constants of the waves travelling within the structure. The wavenumbers and group velocities for waves comprising out of plane structural displacements can then be calculated. Using the numerically extracted wave propagation data the most important SEA quantities of the structure, namely the modal density and the radiation efficiency of each wave type are calculated. The vibroacoustic response of the structure under a broadband diffused excitation is then computed within a SEA approach. The impact of the symmetric and the antisymmetric vibrational motion of the panel on its sound transmission loss is exhibited and the approach proves robust enough for thin as well as for thick layered structures.